Clinical effectiveness of endovascular stroke treatment in the early and extended time windows - Nogueira, Raul G; Haussen, Diogo C; Liebeskind, David S; Jovin, Tudor G; Gupta, Rishi; Saver, Jeffrey L; Jadhav, Ashutosh P; Budzik, Ronald F; Baxter, Blaise; Krajina, Antonin; Bonafe, Alain; Malek, Ali; et al. (International journal of stroke, 2022)
BACKGROUND: The clinical efficacy of mechanical thrombectomy has been unequivocally demonstrated in multiple randomized clinical trials. However, these studies were performed in carefully selected centers and utilized strict inclusion criteria. AIM: We aimed to assess the clinical effectiveness of mechanical thrombectomy in a prospective registry. METHODS: A total of 2008 patients from 76 sites across 12 countries were enrolled in a prospective open-label mechanical thrombectomy registry. Patients were categorized into the corresponding cohorts of the SWIFT-Prime, DAWN, and DEFUSE 3 trials according to the basic demographic and clinical criteria without considering specific parenchymal imaging findings. Baseline and outcome variables were compared across the corresponding groups. RESULTS: As compared to the treated patients in the actual trials, registry-derived patients tended to be younger and had lower baseline ASPECTS. In addition, time to treatment was earlier and the use of intravenous tissue plasminogen activator (IV-tPA) and general anesthesia were higher in DAWN- and DEFUSE-3 registry derived patients versus their corresponding trials. Reperfusion rates were higher in the registry patients. The rates of 90-day good outcome (mRS0-2) in registry-derived patients were comparable to those of the patients treated in the corresponding randomized clinical trials (SWIFT-Prime, 64.5% vs. 60.2%; DAWN, 50.4% vs. 48.6%; Beyond-DAWN: 52.4% vs. 48.6%; DEFUSE 3, 52% vs. 44.6%, respectively; all P > 0.05). Registry-derived patients had significant less disability than the corresponding randomized clinical trial controls (ordinal modified Rankin Scale (mRS) shift odds ratio (OR), P < 0.05 for all). CONCLUSION: Our study provides favorable generalizability data for the safety and efficacy of thrombectomy in the "real-world" setting and supports that patients may be safely treated outside the constraints of randomized clinical trials.
Keywords: tkáňový aktivátor plazminogenu; cévní mozková příhoda; lidé; Endovascular Procedures; endovaskulární výkony; trombektomie; výsledek terapie; registry; Humans; Brain Ischemia; Tissue Plasminogen Activator; Thrombectomy; Stroke; Treatment Outcome; ischemie mozku; thrombectomy